The Efficacy, Safety, and Immunogenicity of Switching Between Reference Biopharmaceuticals and Biosimilars: A Systematic Review. Issue 4 (30th April 2020) - Barbier, Liese; Ebbers, Hans C.; Declerck, Paul; Simoens, Steven; Vulto, Arnold G.; Huys, Isabelle
Abstract : To date, no consensus exists among stakeholders about switching patients between reference biological products (RPs) and biosimilars, which may have been curbing the implementation of biosimilars in clinical practice. This study synthesizes the available data on switching and assesses whether switching patients from a RP to its biosimilar or vice versa affects efficacy, safety, or immunogenicity outcomes. A total of 178 studies, in which switch outcomes from a RP to a biosimilar were reported, was identified. Data were derived from both randomized controlled trials and real‐world evidence. Despite the limitations stemming from a lack of a robust design for most of the studies, the available switching data do not indicate that switching from a RP to a biosimilar is associated with any major efficacy, safety, or immunogenicity issues. Some open‐label and observational studies reported increased discontinuation rates after switching, which were mainly attributed to nocebo effects. Involvement of the prescriber in any decision to switch should remain and attention should be paid to the mitigation of a potential nocebo effect.